2004
DOI: 10.1093/pcp/pch113
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Plant Natriuretic Peptide Causes Rapid and Spatially Differentiated K+, Na+ and H+ Flux Changes in Arabidopsis thaliana Roots

Abstract: Plant natriuretic peptides (PNPs) belong to a novel class of systemically mobile molecules that are structurally similar to the N-terminal domain of expansins and affect physiological processes such as protoplast volume regulation at nano-molar concentrations. Here we demonstrate that AtPNP-A, a recombinant Arabidopsis thaliana PNP causes rapid H(+) influx in the elongation zone of A. thaliana roots but not in the mature zone. AtPNP-A also induces significant K(+) and Na(+) efflux and this effect is seen in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Unlike APs, the amplitude and velocity of the VP varies with distance from the stimulus and is characterized by a longer and more delayed repolarization. It is remarkable then that it has been demonstrated that PNPs can cause membrane depolarization (Maryani et al, 2000), induce ion fluxes (Ludidi et al, 2004) and promote the movement of water out of the xylem (Suwastika and Gehring, 1998). We therefore propose that local AtPNP-A treatment induces an electrical signal that leads to an increase in the rate of dark respiration in systemic leaves.…”
Section: Discussionmentioning
confidence: 87%
“…Unlike APs, the amplitude and velocity of the VP varies with distance from the stimulus and is characterized by a longer and more delayed repolarization. It is remarkable then that it has been demonstrated that PNPs can cause membrane depolarization (Maryani et al, 2000), induce ion fluxes (Ludidi et al, 2004) and promote the movement of water out of the xylem (Suwastika and Gehring, 1998). We therefore propose that local AtPNP-A treatment induces an electrical signal that leads to an increase in the rate of dark respiration in systemic leaves.…”
Section: Discussionmentioning
confidence: 87%
“…Xcc uses a plant natriuretic peptide, XacPNP, to modify host homeostasis and growth (Gottig et al, 2008). PNPs are a class of extracellular, systemically mobile molecules, which elicit multiple plant responses involved in homeostasis and growth, including stomatal opening, water uptake and tissue-specific ion movement (Ludidi et al, 2004;Maryani et al, 2001;Pharmawati et al, 2001). XacPNP has no known homologue in other bacteria (Gottig et al, 2008).…”
Section: Host-pathogen Interaction and Infection Processmentioning
confidence: 99%
“…Variation potentials do not involve voltage gated channels and their amplitude and velocity alters with distance from the stimulus and they have longer and more delayed repolarization periods than action potentials. The "electrical signal" hypothesis is supported by the previous findings that PNPs can cause rapid and significant membrane depolarization, 23 induce rapid ion fluxes 24,25 as well as promote the movement of water out of the xylem. 26 In conclusion, since local increases of PNP can have marked influences on plant function distantly, 5 it therefore becomes evident that for the plant it is highly important to maintain levels of PNP within a defined range at the local level where it is produced.…”
Section: Feedback-regulation Of Pnp Productionmentioning
confidence: 77%